The Impact of Control Systems on Corporate Innovation† - Miller, Brian P.; Sheneman, Amy G.; Williams, Brian M. (Contemporary Accounting Research, 2022)
ABSTRACT This study examines the impact of control systems on corporate innovation. Innovation is key to firm performance and growth, allowing corporations to stay competitive in their industry. We expect control systems to improve information flows within the firm by allowing managers to better identify and patent their most valuable intellectual property. Despite our prediction that control systems positively impact innovation, a priori, this relation is unclear as these same control systems may create an overly restrictive bureaucratic environment that may mitigate the benefits of effective controls for innovation. Using various measures of control system quality, we find evidence that effective control systems are associated with more innovation. Overall, the results of our study suggest effective control systems are associated with the ability of a firm to leverage its innovative projects. Our results suggest that corporations with effective control systems are more likely to be able to react to market and technology changes by ensuring their best ideas are patented.